Newspaper coverage of biobanks - Ubaka Ogbogu; Maeghan Toews; Adam Ollenberger; Pascal Borry; Helene Nobile; Manuela Bergmann; Timothy Caulfield (PeerJ, 2014)
Background. Biobanks are an important research resource that provides researchers with biological samples, tools and data, but have also been associated with a range of ethical, legal and policy issues and concerns. Although there have been studies examining the views of different stakeholders, such as donors, researchers and the general public, the media portrayal of biobanks has been absent from this body of research. This study therefore examines how biobanking has been represented in major print newspapers from Australia, Canada, the United Kingdom and the United States to identify the issues and concerns surrounding biobanks that have featured most prominently in the print media discourse.Methods. Using Factiva, articles published in major broadsheet newspapers in Canada, the US, the UK, and Australia were identified using specified search terms. The final sample size consisted of 163 articles.Results. Majority of articles mentioned or discussed the benefits of biobanking, with medical research being the most prevalent benefit mentioned. Fewer articles discussed risks associated with biobanking. Researchers were the group of people most quoted in the articles, followed by biobank employees. Biobanking was portrayed as mostly neutral or positive, with few articles portraying biobanking in a negative manner.Conclusion. Reporting on biobanks in the print media heavily favours discussions of related benefits over risks. Members of the scientific research community appear to be a primary source of this positive tone. Under-reporting of risks and a downtrend in reporting on legal and regulatory issues suggests that the print media views such matters as less newsworthy than perceived benefits of biobanking.